ECONOMIC GROWTH AND PERCAPITA INCOME DISTRIBUTION: CASE STUDY OF EAST JAVA PROVINCE - I Made Suparta (Universitas Islam Indonesia, 2010)
The objective of this paper is of twofold. First, it analyzes the disparity distribution of percapitaincome among regions in East Java Province. Second, it analyzes the correlation beetwen economicgrowth and disparity distribution of percapita income among regions in East Java Province. It usesWilliamson disparity index and Pearson correlation to analyze the data. In the period of 2001-2007,the disparity index shows that distribution of percapita income among regions in East Java Provinceis getting unbalanced and the correlation beetwen economic growth and disparity distributionof percapita income among regions in East Java Province is positive and significant.Keywords: Income per capita, disparity, economic growthJEL classification numbers: O16, O18, O49